(De)contextualizing the dictator's son a content analysis on the media's coverage of President Ferdinand "Bongbong" Marcos first 100 days - Cruz, Alison Caitlin; Tarras, Godfrey Jesse
This qualitative study employed conceptual content analysis to look into how online newspaper brands Philstar, INQUIRER.NET, and Manila Bulletin provided context in their daily coverage of the first 100 days of President Ferdinand "Bongbong" Marcos Jr., given Marcos' direct link to the former dictator Ferdinand Marcos Sr., as well as how he benefited from mis- and disinformation to win as president. To determine how context was supplied, the researchers crafted categories for contextualization which are "distorted, "insufficient," "uncritical," and "absent." News Framing was also utilized to see how the chosen news brands highlighted which aspects of the stories to focus on about Marcos' governance during his first 100 days. The study found that, by the researchers' standards, all three newspapers had high averages of distorted, insufficient, and uncritical contextualization and were inconsistent and tame in providing historical background surrounding the Marcos name.